Theoretical model of shear capacity of steel fiber reinforced concrete beams. (1st April 2023) - Lantsoght, Eva O.L.
Highlights: The presented model considers the effect of steel fibers on all shear-carrying mechanisms in SFRC beams failing in shear. The model performs satisfactorily when compared to a database of SFRC beams failing in shear. The model does not contain any new empirical elements and is fully based on theory. The paper identifies ways forward to improve this model based on targeted experiments. Abstract: One of the barriers to implementation of steel fiber reinforced concrete (SFRC) into structural applications is the lack of understanding of the shear behaviour of SFRC members. This paper proposes a theoretical model for the shear capacity of SFRC members with mild steel reinforcement based on the shear-carrying mechanisms and sectional analysis. The model is derived completely theoretically, based on concepts from the literature, and does not include new empirical aspects. The approach is then compared to 323 experiments from the literature of beams with slender, rectangular cross-sections failing in shear. It is found that the model is slightly conservative, and experimental research necessary to further develop the model is described. The presented theory aims to be a framework for a fully theoretical description of the shear capacity of SFRC members with longitudinal reinforcement and without shear reinforcement.